PENGARUH EKONOMI KREATIF DAN SEKTOR PARIWISATA TERHADAP PERTUMBUHAN EKONOMI KABUPATEN BERAU - ELSA MAULIDIA (Prodi Ekonomi Pembangunan, Universitas Muhammadiyah Berau, 2026)
Background: Economic growth is a key indicator of regional development success, reflected in the increase of Gross Regional Domestic Product (GRDP). In the modern era, the creative economy plays an important role in supporting the tourism sector through human resource innovation and creativity, while tourism serves as a strategic sector capable of raising community income and welfare. Berau Regency holds substantial potential in both sectors, yet their empirical contribution to regional economic growth has rarely been studied. Objective: This study aims to determine the partial and simultaneous effects of the creative economy and the tourism sector on economic growth in Berau Regency. Method: The method used is multiple linear regression analysis with time series data from 2014–2023 (N=10) obtained from the Central Statistics Agency (BPS), using a saturated sampling technique. The classical assumption tests confirm the regression model is free from multicollinearity, heteroscedasticity, and autocorrelation. Results: The results show that the GRDP of the creative economy has a positive and significant partial effect on economic growth, while the number of tourist visits has a positive but not significant partial effect. Simultaneously, both variables significantly affect economic growth, with a correlation coefficient (R) of 0.959 and a coefficient of determination (R²) of 0.920, indicating that 92% of the variation in economic growth is explained by the two variables. Conclusion: It is concluded that the creative economy and tourism sector should be developed in an integrated manner to promote inclusive and sustainable economic growth in Berau Regency.